Consequences and determinants of poor nutrition in children aged 0-3 years, and public health interventions that may improve dietary intake: a general review. Issue 2 (10th June 2014) - Barlow, Jane; Summerbell, Carolyn; Moore, Helen; O'Malley, Claire
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review the evidence base for effective public health interventions which aim to improve the diet of children aged zero to three years. Design/methodology/approach – General review. Findings – Key approaches and components of effective interventions include: repeated tasting, parental modelling, use of rewards, moderate restriction of "unhealthy" foods alongside an increase in portion sizes of fruits and vegetables, culturally appropriate messages, culturally acceptable health care provider, sufficient intensity of intervention, and an intervention which targets parental self-efficacy and modelling. Interventions which provide home visits (rather than require visits to a GP surgery or local community centre) financial incentives and/or mobile phone reminders may increase retention, particularly for some individuals. Recruiting mothers into programmes whilst they are pregnant may improve recruitment and retention rates. Originality/value – Allows for key public health interventions, approaches and components to be explored and identified. This will ensure that there is guidance to inform the development of new interventions for this age group and more importantly recommend that those components which are most successful be incorporated in policy and practice.